Validity of Barium Enema as Hirschsprung’s Disease Diagnostic Tools for Infant in Sanglah Hospital Denpasar - Darmajaya, I Made; Subhawa, I Ketut (JBN (Jurnal Bedah Nasional), 2021)
Aim : To determine the validity (sensitivity, specificity, likelihood ratio) of barium enema as Hirschsprung's disease diagnostic tool in infants. Methods: This study was a diagnostic test of barium enema compared with postoperative histopathology examinations as the gold standard. The population were all patients with indigestion symptom be discovered at the pediatric surgical clinic of Sanglah Hospital Denpasar. The sampling method was consecutive sampling, satisfy inclusion criteria (< 12 months old, indicate classic symptoms of Hirschsprung’s disease). The total sample of the study was 52 patients. Sensitivity, specificity, positive and negative predictive value were analysed using cross-tabulation test of barium enema and postoperative histopathology. Results: A total of 52 patients were evaluated during the study period, mean of age was 3.31 months old, and boys:girls (75%:25%). Based on symptoms, 98.08% of patients were delayed release of meconium more than 24-48 hours and abdominal distention. Among all the patients reviewed, sensitivity, specificity, positive and negative predictive value of barium enema for diagnostic of Hirschsprung’s disease was 95.5%, 87.5%, 97.7%, and 77.8%. Conclusion: Barium enema can be used as an early diagnostic tool for infants suspected of Hirschsprung’s disease.